2021
DOI: 10.1093/ehjcvp/pvab056
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-renal benefits of sodium–glucose co-transporter 2 inhibitors in heart failure with reduced ejection fraction: mechanisms and clinical evidence

Abstract: The heart and the kidneys are closely interconnected, and disease in one organ system can lead to disease in the other. This interdependence is illustrated in heart failure with reduced ejection fraction (HFrEF), where worsening heart failure can lead to renal dysfunction and vice versa. Further complicating this situation is the fact that drugs that serve as guideline directed medical therapy (GDMT) for HFrEF can affect renal function. Sodium glucose co-transporter 2 (SGLT2) inhibitors are a new class of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…[ 26 28 ] The osmotic diuresis with resultant free water loss has been projected to explain the beneficial relatively higher interstitial versus intravascular fluid losses with a reduced reflexive neurohormonal activation thought to make SGLT2is unique when compared with conventional diuretics. [ 20 , 29 , 30 ] SGLT2i-induced osmotic diuresis may improve myocardial oedema by increasing plasma oncotic pressure and stimulating plasma refill, thereby pulling fluid from the cardiac interstitium through Starling's forces. [ 25 ] A reduction in myocardial oedema is associated with a rightward shift in end-diastolic pressure volume relationship with decreases in left ventricular (LV) mass on cardiac magnetic resonance, and may be contributory in the early improvement of functional status demonstrated by PRESERVED-HF and CHIEF-HF, and may also partly explain EMPEROR-Preserved reaching significance in just 18 days with a reduction in worsening HF events.…”
Section: Proposed Mechanisms Of Action Of Sglt2is In Hfpefmentioning
confidence: 99%
“…[ 26 28 ] The osmotic diuresis with resultant free water loss has been projected to explain the beneficial relatively higher interstitial versus intravascular fluid losses with a reduced reflexive neurohormonal activation thought to make SGLT2is unique when compared with conventional diuretics. [ 20 , 29 , 30 ] SGLT2i-induced osmotic diuresis may improve myocardial oedema by increasing plasma oncotic pressure and stimulating plasma refill, thereby pulling fluid from the cardiac interstitium through Starling's forces. [ 25 ] A reduction in myocardial oedema is associated with a rightward shift in end-diastolic pressure volume relationship with decreases in left ventricular (LV) mass on cardiac magnetic resonance, and may be contributory in the early improvement of functional status demonstrated by PRESERVED-HF and CHIEF-HF, and may also partly explain EMPEROR-Preserved reaching significance in just 18 days with a reduction in worsening HF events.…”
Section: Proposed Mechanisms Of Action Of Sglt2is In Hfpefmentioning
confidence: 99%
“…Several clinical trials have demonstrated that SGLT2 inhibitors cause a significant reduction in HF hospitalization ( 268 270 ). These beneficial effects on HFrEF patients persist even in non-diabetic patients as was reported by DAPA-HF and EMPEROR-Reduced trials ( 271 273 ).…”
Section: Edema Therapy In Heart Failurementioning
confidence: 99%
“…In recent years, more and more evidence shows that hypoglycemic drugs also have cardiovascular benefits [ 10 , 11 ]. Sodium-glucose cotransporter-2 inhibitors (SGLT2is), including empagliflozin, dapagliflozin, canagliflozin, and ertugliflozin, show a good prospect in the treatment of HF [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%